(untitled) (Palimpsesto, 2023)
Through an autoethnography, the main tensions and problems related to the Collective Bargaining developed by the Union of the Universidad Academia Humanismo Cristiano with the authorities of said house of study, in the years 2020 and 2023, are revealed. be a front-line precedent, updated, contingent and with bibliographic review, on how the Collective Bargaining regulated in Chile, serves (or not) as a tool of struggle, of salary improvements and working conditions, for workers of the institutions of Higher Education in Chile, specifically private Universities.